THE ROLE OF SPIRITUALITY AND TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL RESILIENCE - Purbiyati, Yuliana Sri; Tjahjono, Monica Candra (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2024)
This research examines the influence of spirituality in the workplace and transformational leadership, organizational resilience. This research also tests transformational leadership as a mediating variable on the influence of workplace spirituality on organizational resilience. This research uses a survey questionnaire. The research sample was determined based on the table of Krejcie et al. (1970), namely if the population is 100 then the sample is 80. The research sample consisted of 80 educators and education staff from Catholic high schools in the city of Surabaya. This research uses partial least squares structural equation modeling (PLS-SEM) to test the hypothesis. The findings of this research are that there is a significant relationship between workplace spirituality and organizational resilience, both directly and indirectly mediated by transformational leadership. This research has practical implications for school principals and school administrators to realize the benefits of spirituality and transformational leadership in building organizational resilience in schools. Further research is still needed to examine the influence of workplace spirituality and transformational leadership on organizational resilience in schools to provide new insights into the role of workplace spirituality and transformational leadership in building school organizational resilience.